The Relationship between Modern Self-development on Work Success of Support Personnel at Mahasarakham University - Inounchot, Cholticha; Inounchot, In (Journal of Roi Et Rajabhat University, 2023)
The purpose of this research was to study the relationship between modern self-development on work success of support personnel at Mahasarakham University by using a questionnaire as an instrument for collecting data from 218 support personnel. The statistics used for data analyses were percentage, mean, multiple correlation analysis, simple regression analysis and multiple regression analysis. The results of the research revealed that the support personnel’s opinion on modern self-development overall and each aspect including attitude, skill training, and knowledge enhancement, were at a high level, The support personnel ‘s opinion on work success overall and each aspect, including achievement, job satisfaction, job stability, and job recognition. were at a high level. According to analyses of correlation and effect, they were found that the modern self-development in the aspects of knowledge enhancement and attitude correlated and positive effect on overall work success, therefore, Mahasakham University Administrators should focus on enhancing knowledge and attitude for job experts and morale of support personnel those affect the effective work success of the university.